Formação profissional e as primeiras experiências docentes: desafios e possibilidades na constituição de ser professor no contexto da educação do campo - Dias, Yanka Pereira (Brasil, 2025)
The process of acquiring experiences in the field of teaching is essential to understand the complexities and challenges faced by teachers from their training to their performance in the classroom. Thus, this study has as its main objective to understand the first teaching experiences in rural schools, considering the specificities and challenges of the Amazonian context. The identification of the reasons that lead many graduates of the Pedagogy course at ICSEZ/UFAM to start their professional career in rural schools is fundamental to understand the factors that influence this choice, whether for personal, social or professional reasons. In this context, the research considers that the teacher is the mediator of knowledge and cannot be neutral in his relationship with the students, and it is necessary to take into account the social characteristics and needs of each student. To achieve the proposed objectives, this study adopted a qualitative approach, with the objective of understanding the first teaching experiences in rural schools and the impacts of these experiences on the formation of teachers' professional identity, consisting of semi-structured interviews, which allowed participants to freely discuss their experiences. The study was developed in the communities of the Lower Amazon, where rural education is of great relevance, but is still undervalued. This study, therefore, provides important contributions to the understanding of the initial and continuous training of teachers who work in rural schools, emphasizing the need for a formative approach that takes into account the particularities of the rural context. In addition, it highlights the importance of public policies that strengthen education in the countryside and promote the appreciation of education professionals, ensuring adequate conditions for the development of their practice and their permanence in rural areas. In addition, it highlights the importance of public policies that strengthen education in the countryside and promote the appreciation of education professionals, ensuring adequate conditions for the development of their practice and their permanence in rural areas. The results revealed that teachers in the region, despite their dedication, face difficulties due to the lack of infrastructure, institutional support and the scarcity of adequate pedagogical materials. In addition, it was observed that the cultural, social and political specificities of these communities directly impact the teaching-learning process.